Respostas auton??micas e cardiovasculares em voo e sua rela????o com a aptid??o f??sica - Silva, Irans?? Oliveira (2016)
Aviation is the most effective means of transportation that exists today, serving billions of people every year. However stressors present in air travel cause autonomic changes occur, requiring the body an ability to deal with these factors. Therefore preventive and/or mitigating strategies of these effects need to be understood. The study aims to evaluate the autonomic and cardiovascular responses that occur in flight and its relationship to physical fitness. The research was done through two studies, where healthy men had the components of physical fitness: aerobic capacity, muscular strength and body fat previously evaluated; and the registration of heart rate variability (HRV) performed in a control day and a flight day. The first study 11 fighter pilots reported 3h HRV and had the level of dehydration during a test flight measured by hematocrit change. The flight lasted 1 hour and all underwent the same operating procedures. The second study, 22 passengers of commercial aviation, recorded 24h HRV and blood pressure simultaneously. The results of the study show that a supersonic flight caused a reduction in most HRV parameters during flight when compared with the control day. There is no autonomic anticipation. Entropy correlated with aerobic capacity and body fat. Dehydration generated by the flight changed HRV (RMSSD and SD1). The second study demonstrates that the commercial flight caused a reduction in most HRV parameters during flight (RMSSD; SD1; SampEn; LnHF; 1), and in 24h when compared with control day (FC; LnHF; 2). There was autonomic anticipation. The blood pressure and Rate-Pressure Product were significantly higher on the flight, with the largest increases two hours before the flight and staying elevated for up to two hours. The lower the body fat percentage and BMI, the greater the HRV during the flight day (RMSSD; LF; HF; SD1). Already the aerobic capacity the higher, the greater the HRV during the flight (LnLF; LnHF). Conclusions: The flight, in both situations and people, demanded the body autonomic responses generating significant vagal withdrawal, an increase in heart rate. The body fat and aerobic capacity, indicators of physical fitness, correlated with HRV, however differently in the two populations and situations: fighter pilots (SampEn) and passengers of commercial aviation (RMSSD; LF; HF; SD1). Dehydration generated by supersonic flight influence on HRV. The blood pressure (SBP, DBP, MAP) is influenced by virtue of flight in comparison of 24h. The autonomic changes relating correlate with aerobic capacity and body fat differently in pilots of supersonic jets and passenger commercial aircraft undergoing flight. The relative strength was not correlated with HRV parameters in any of the populations studied.